Let S n be the set of all the numbers of the form ϵ n 3 + ϵ n − 1 3 + . . . + ϵ 2 3 + ϵ 1 3 where the number of radicals is an arbitrary non-negative integer number n and ϵ k = ± 1 for any non-negative integer k less than or equal to n . If you can express the elements of S 1 2 like a finite increasing sequence of numbers { r 0 , r 1 , r 2 , . . . , r m − 1 } , where m is the number of distinct numbers in S 1 2 , then find ⌊ − 1 0 0 0 r 2 0 2 1 ⌋ , otherwise, enter 555.
Note : ⌊ x ⌋ denotes the floor of the number x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Wonderful work, @Alexander McDowell !
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 |
|
Given an arbitrary positive integer number
n
, we can define the following function
f
n
:
S
n
→
{
0
,
1
,
2
,
.
.
.
,
2
n
−
1
}
by the following rule
f
n
(
a
n
3
+
a
n
−
1
3
+
.
.
.
+
a
1
3
)
=
(
α
n
α
n
−
1
.
.
.
α
1
)
2
,
where the expression in the right side of the following equation is a binary number defined on the following way
For any integer
k
greater than or equal to 1 and less than
n
,
α
k
=
{
1
,
0
,
if
a
n
a
n
−
1
.
.
.
a
k
=
1
if
a
n
a
n
−
1
.
.
.
a
k
=
−
1
.
We can see that
f
n
is well-defined and has an inverse function that can be defined in the following way
f
n
−
1
(
α
n
α
n
−
1
.
.
.
α
1
)
2
=
a
n
3
+
a
n
a
n
−
1
3
+
.
.
.
+
a
2
a
1
3
,
where
a
k
=
{
1
,
−
1
,
if
α
k
=
1
if
α
k
=
0
.
Now, we are going to use Mathematical Induction to prove the following equivalence.
a n 3 + a n − 1 3 + . . . + a 1 3 < b n 3 + b n − 1 3 + . . . + b 1 3 ⟺ f n ( a n 3 + a n − 1 3 + . . . + a 1 3 ) < f n ( b n 3 + b n − 1 3 + . . . + b 1 3 ) ( ∗ ) Notice that the symbol "<" represent the regular order of the set of numbers. Of course, this property is obviously true when n = 1 .
Assume that the equivalence is true if n = k , and we must prove that it is true when n = k + 1 . To prove (*) for n = k + 1 let us consider two numbers a k + 1 3 + a k 3 + . . . + a 1 3 and b k + 1 3 + b k 3 + . . . + b 1 3 in S k + 1 . Let us consider also that f k + 1 ( a k + 1 3 + a k 3 + . . . + a 1 3 ) = ( α k + 1 α k . . . α 1 ) 2 and f k + 1 ( b k + 1 3 + b k 3 + . . . + b 1 3 ) = ( β k + 1 β k . . . β 1 ) 2 , where the α k ′ s and the β k ′ s are defined as we did it above. We are going to divide the proof in the following cases.
Case 1. a k + 1 = − 1 and b k + 1 = 1 .
The equivalence (*) is true due to the fact that ( a k + 1 = − 1 and b k + 1 = 1 ) ⟺ ( α k + 1 = 0 and β k + 1 = 1 )
Case 2. a k + 1 = b k + 1 = 1 . In this case, it is easy to see that if f k + 1 ( 3 + a k 3 + . . . + a 1 3 ) = ( 1 α k . . . α 1 ) 2 and f k + 1 ( 3 + b k 3 + . . . + b 1 3 ) = ( 1 β k . . . β 1 ) 2 , then f k ( a k 3 + . . . + a 1 3 ) = ( α k . . . α 1 ) 2 and f k ( b k 3 + . . . + b 1 3 ) = ( β k . . . β 1 ) 2 , and vice-versa.
Then we can prove the equivalence (*) for n = k + 1 in the following way. The condition 3 + a k 3 + . . . + a 1 3 < 3 + b k 3 + . . . + b 1 3 is equivalent to a k 3 + . . . + a 1 3 < b k 3 + . . . + b 1 3 by the definition of the order on M k + 1 . Using the hypothesis of induction the last inequality is equivalent to ( α k . . . α 1 ) 2 < ( β k . . . β 1 ) 2 , and this one is equivalent to f k + 1 ( 3 + a k 3 + . . . + a 1 3 ) < f k + 1 ( 3 + b k 3 + . . . + b 1 3 ) .
Case 3. a k + 1 = b k + 1 = − 1 . In this case, it also easy to see that f k + 1 ( − 3 + a k 3 + . . . + a 1 3 ) = ( α k , . . . , α 1 ) 2 and f k + 1 ( − 3 + b k 3 + . . . + b 1 3 ) = ( β k . . . β 1 ) 2 . In turn, these two equations are equivalent to f k ( a k 3 + . . . + a 1 3 ) = ( t k . . . , t 1 ) 2 and f k ( b k 3 + . . . + b 1 3 ) = ( t k , . . . , t 1 ) 2 , where t k = { 0 , 1 , if α k = 1 if α k = 0 . and s k = { 0 , 1 , if β k = 1 if β k = 0 . Now the equivalence (*) can be proved in a simple way for n = k + 1 . The condition − 3 + a k 3 + . . . + a 1 3 < − 3 + b k 3 + . . . + b 1 3 is equivalent to b k 3 + . . . + b 1 3 < a k 3 + . . . + a 1 3 . The last inequality is equivalent to f k ( b k 3 + . . . + b 1 3 ) < f k ( a k 3 + . . . + a 1 3 ) , by the hypothesis of induction, and using the definitions of the t k ′ s and s k ′ s that we introduced above , this last inequality is equivalent to f k + 1 ( − 3 + a k 3 + . . . + a 1 3 ) < f k + 1 ( − 3 + b k 3 + . . . + b 1 3 ) .
Then the proof of (*) is complete.
From the property (*), we can obtain that f n is not only bijective, but it also keeps the order. Therefore, in the case that n = 1 2 , we have that l k = f 1 2 − 1 ( k ) , where k is an integer satisfying 0 ≤ k ≤ 2 1 2 − 1 = 4 0 9 5 . Now using that f 1 2 − 1 ( ( α 1 . . . α 1 1 ) 2 ) = ( a 1 2 3 + a 1 2 a 1 1 3 + . . . + a 2 a 1 3 ) as it was defined above, and that the binary representation of 2021 is ( 0 1 1 1 1 1 1 0 0 1 0 1 ) 2 , we obtain that f 1 2 − 1 ( 2 0 2 1 ) = − 3 − 3 + 3 + 3 + 3 + 3 + 3 − 3 + 3 − 3 − 3 − 3 = − 0 . 8 3 5 4 . . . So the answer is 8 3 5 .
Problem Loading...
Note Loading...
Set Loading...
Let E n represent the set of possible ϵ k for an integer k less than equal to n where the corresponding r m is sorted from lowest to highest (I will abbreviate − 1 as − and 1 as + ). For instance, E 2 = { [ − , + ] , [ − , − ] , [ + , − ] , [ + , + ] } with corresponding set of r m of { − 3 + 3 , − 3 − 3 , 3 − 3 , 3 + 3 } . The i th element of E n corresponds to ϵ n − i + 1 (e.g: 1st element equals ϵ n and last element equals ϵ 1 ). I started by listing out S n for various small values of n using brute-force:
Using a Python script, I also computed E 4 and E 5 but I figured that the sizes of these sets would be too large to display in this post ( ∣ E 4 ∣ = 1 6 and ∣ E 5 ∣ = 3 2 ).
After listing these sets, I noticed several repeated patterns. First, look at the last number of each of the sets ( ϵ 1 ) with n > 1 . For E 2 , the sequence of ϵ 1 values is { + , − , − , + } . For E 3 , the sequence is { + , − , − , + , + , − , − , + } . In general for n > 1 , ϵ 1 alternates between groups of two − and groups of two + beginning with a group of 1 + . We can model this sequence for the i th ( i ≥ 1 ) set of E n given n > k with the function f 1 ( i ) = ( − 1 ) f l o o r ( 2 m o d ( i , 4 ) ) (check values yourself to confirm that it works).
Next, we'll look at the sequence of ( ϵ 2 ) with n > 2 . For E 3 , the sequence is { + , + , − , − , − , − , + , + } . For E 4 , the sequence is { + , + , − , − , − , − , + , + , + , + , − , − , − , − , + , + } . In general for n > 2 , ϵ 2 alternates between groups of four − and groups of four + beginning with a group of 2 + . We can model this sequence for the i th ( i ≥ 1 ) set of E n given n > k with the function f 2 ( i ) = ( − 1 ) f l o o r ( 4 m o d ( i + 1 , 8 ) )
Looking at the sequences for ϵ 3 and ϵ 4 , it turns out that for n > k , ϵ k alternates between groups of 2 k − and groups of 2 k + beginning with a group of 2 k − 1 + . We can generalize this with the function f ( i , k ) = ( − 1 ) f l o o r ( 2 k m o d ( i + 2 k − 1 − 1 , 2 k + 1 ) ) to find the value of ϵ k for the i th ( i ≥ 1 ) set of E n given n > k .
Now what about k = n ? Well, let's look at the sequences of ϵ n for each E n . For E 1 , the sequence of ϵ 1 is { − , + } , for E 2 , the sequence of ϵ 2 is { − , − , + , + } , and for E 3 , the sequence of ϵ 3 is { − , − , − , − , + , + , + , + } . We quickly see that the sequence for ϵ n starts with 2 n − 1 groups of − followed by 2 n − 1 groups of + . The general formula for ϵ n for the i th ( i ≥ 1 ) set of E n is g ( i , n ) = ( − 1 ) 1 + f l o o r ( 2 ( n − 1 ) i − 1 ) .
We now have the tools we need to compute r 2 0 2 1 for n = 1 2 . Firstly, we generate the 2022th index of E 1 2 (since r starts counting at 0 not 1) using f ( 2 0 2 2 , k ) with 1 ≤ k < 1 2 and g ( 2 0 2 2 , 1 2 ) . This means that ϵ 1 = f ( 2 0 2 2 , 1 ) , ϵ 2 = f ( 2 0 2 2 , 2 ) , ϵ 3 = f ( 2 0 2 2 , 3 ) , ..., ϵ 1 2 = g ( 2 0 2 2 , 1 2 ) . This list of ϵ k is [ − 1 , − 1 , − 1 , 1 , − 1 , 1 , 1 , 1 , 1 , 1 , − 1 , − 1 ] . Plugging this into the nested radical expression (I used a Python script for this) gives r 2 0 2 1 = − 0 . 8 3 5 4 2 2 . Thus, ⌊ − 1 0 0 0 r 2 0 2 1 ⌋ = 8 3 5 .
I imagine that the proof for why this pattern emerges is more complicated than simply identifying the pattern.